Typhoid fever and genetic polymorphisms at the natural resistance-associated macrophage protein 1. - Dunstan, S; Ho, V; Duc, C; Lanh, M; Phuong, C; Luxemburger, C; Wain, J; Dudbridge, F; Peacock, C; House, D; Parry, C; Hien, T; et al. (2001)
Control of Salmonella enterica serovar Typhimurium (S. typhimurium) infection in the mouse model of typhoid fever is critically dependent on the natural resistance-associated macrophage protein 1 (Nramp1). In this study, we examined the role of genetic polymorphisms in the human homologue, NRAMP1, in resistance to typhoid fever in southern Vietnam. Patients with blood-culture-confirmed typhoid fever and healthy control subjects were genotyped for 6 polymorphic markers within and near NRAMP1 on chromosome 2q35. Four single base-pair polymorphisms (274 C/T, 469+14 G/C, 1465-85 G/A, and D543N), a (GT)(n) repeat in the promoter region of NRAMP1 and D2S1471, and a microsatellite marker approximately 130-kb downstream of NRAMP1 were examined. The allelic and genotypic frequencies for each polymorphism were compared in case patients and control subjects. No allelic association was identified between the NRAMP1 alleles and typhoid fever susceptibility. In addition, neither homozygotes nor heterozygotes for any NRAMP1 variants were at increased risk of typhoid fever.